Cutaneous Reconstruction of the Nasal Distal Third: Alternative Local Flaps for a Complex Region. Issue 5 (May 2021) - Cason, Roger W.; Shammas,, Ronnie L.; Pyfer, Bryan J.; Glener, Adam D.; Marcus, Jeffrey R.; Cook, Jonathan L.
Abstract : Summary: Small-to-medium cutaneous defects of the distal nose pose a significant challenge to reconstructive surgeons, and commonly described reconstructive techniques have their limitations. As the skin of this region is characteristically rigid and sebaceous, care must be taken to avoid introducing unfavorable tension vectors that can result in functional or anatomic distortion of the nasal free margins. With this in mind, the authors discuss 3 alternative reconstructive options, the East-West, nasalis sling, and trilobed flaps, which have wide utility in the repair of distal nasal cutaneous defects and can result in excellent cosmesis. The indications, surgical technique, and limitations of each are discussed in detail, and are compared with several of the more commonly described options in the context of distal nasal reconstruction.